Recovery of silver residues from dental amalgam - Pereira, Heloísa Aparecida Barbosa da Silva; Iano, Flávia Godoy; da Silva, Thelma Lopes; de Oliveira, Rodrigo Cardoso; de Menezes, Manoel Lima; Buzalaf, Marília Afonso Rabelo (FapUNIFESP (SciELO), 2010)
Dental amalgam residues are probably the most important chemical residues generated from clinical dental practice because of the presence of heavy metals among its constituents, mainly mercury and silver. Objective: The purpose of this study was to develop an alternative method for the recovery of silver residues from dental amalgam. Material and Methods: The residue generated after vacuum distillation of dental amalgam for the separation of mercury was initially diluted with 32.5% HNO3, followed by precipitation with 20% NaCl. Sequentially, under constant heating and agitation with NaOH and sucrose, the sample was reduced to metallic silver. However, the processing time was too long, which turned this procedure not viable. In another sequence of experiments, the dilution was accomplished with concentrated HNO3 at 90°C, followed by precipitation with 20% NaCl. After washing, the pellet was diluted with concentrated NH4OH, water and more NaCl in order to facilitate the reaction with the reducer. Results: Ascorbic acid was efficiently used as reducer, allowing a fast reduction, thus making the procedure viable. Conclusions: The proposed methodology is of easy application and does not require sophisticated equipment or expensive reagents.
Keywords: Dental amalgam; Environment; Silver; Solid wastes